[Comment] Hospitalization experiences and post-traumatic stress in inflammatory bowel disease: opportunities for change - Dai Lian; Zhu Ping (结直肠肛门外科)
[Introduction] Medical trauma related to IBD (IBD-PTS) affects approximately 25% of patients and is associated with poor outcomes. Prior studies identify common hospitalization experiences as potentially traumatic but have not measured risk relationships for the development of IBD-PTS. We aim to investigate what aspects of hospitalizations may increase the chance of medical trauma and IBD-PTS development. [Methods] Adult patients with IBD enrolled in the IBD Partners database were recruited. Study specific questionnaires included PTSD checklist, 5th edition (PCL-5), patient experience questionnaire, and items about the patient's most stressful hospitalization and nonhospital sources of medical trauma. Established criteria for the PCL-5 identified significant IBD-PTS symptoms (re-experiencing, avoidance, mood change, hyperarousal, global diagnosis). Select disease and treatment information was obtained from the main IBD Partners dataset. Univariate and multivariate statistics evaluated the relationships between hospitalization data and IBD-PTS. [Results] There were 639 participants with at least 1 hospitalization for IBD included. Approximately two-thirds had Crohn's disease; most were White, non-Hispanic, female, middle-aged, and reported their IBD as being in remission. Forty percent of patients stated a hospitalization was a source of IBD-PTS. Frequent anxiety while hospitalized increased the odds of IBD-PTS 2 to 4 times; similar relationships existed for pain/pain control. Higher quality communication, information, and listening skills reduced the odds of IBD-PTS, albeit marginally. [Conclusions] Patients with IBD consistently cite hospitalizations as potential sources of medical trauma. Poorly managed anxiety and pain demonstrate the greatest chance for IBD-PTS development. Gender and racial/ethnic differences emerged for these risks. Positive interactions with the medical team may help mitigate in-hospital IBD-PTS development.